Polemic over the Rejection of the Presence of the Israeli National Team which Led to the Cancellation of Indonesia as the Host of the U-20 World Cup - Imelda Martinelli; Gilbert Winata; Ilhan Pasha Islamy Trisnadi (CV. Rayyan Dwi Bharata, 2023)
Football is one of the biggest sports in the world, until now it has become a very large industry and involves a lot of money, including the large salaries of players in work agreements, and Indonesia is no exception. This phenomenon attracts attention not only for sponsors in terms of business, but for political actors as well as part of the political media for them. Football for some political elites is considered as a medium or a tool for them to communicate with audiences in the electoral politics sphere. This is done by conveying political information through a popular medium for many people, namely football. In this way, it can be understood that football also has its own spirit in the process of political constellation in Indonesia. The rapid development of football has made this sport a source as well as a tool to achieve certain goals. The goals can vary, ranging from the acquisition of capital capital to power, existence and ideologicalization. The goals desired through football were carried out by propaganda techniques that made it possible to achieve a desired goal. In essence, football and politics are two things that are identical but not the same. These two things are two battles to fight over something that has high intrinsic value. The rejection of the presence of the Israeli national team in the U-20 World Cup which led to the cancellation of Indonesia as the host led to various legal polemics and involved complex legal aspects. In this journal, we will discuss aspects of civil law using applicable laws in Indonesia regarding the cancellation.